(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Oral fluid is a unique biological medium. Determination of parameters in oral fluid has a number of advantages over traditional blood testing methods: non-invasiveness, atraumaticity for the patient, absence of stress inherent in venipuncture; easier storage and transportation conditions due to the liquid state (unlike whole blood, which is subject to coagulation processes); the ability to obtain the required amount of biological material; the absence of the need for qualified personnel and special equipment when obtaining oral fluid, which allows its practical use in express laboratories of various directions. Despite the attention paid to the diagnostic value of oral fluid, the problems of studying its parameters are mainly due to the lack of systematized data on the role of specific biomolecules in the diagnosis of diseases in clinical practice. The lack of highly sensitive diagnostic systems also affects. However, interest in the study of oral fluid has not subsided at present, and a number of works are devoted to non-invasive research methods.